2012
DOI: 10.1002/ajmg.a.35621
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial deletion of 11q‐implicating the KIRREL3 gene in the neurocognitive delay associated with Jacobsen syndrome

Abstract: Jacobsen syndrome (JS) is a rare contiguous gene disorder characterized by a deletion within the distal part of the long arm of chromosome 11 ranging in size from 7 to 20 Mb. The clinical findings include characteristic dysmorphic features, growth and psychomotor delays and developmental anomalies involving the brain, eyes, heart, kidneys, immune, hematologic, endocrine, and gastrointestinal systems. The majority of cases are due to a terminal deletion of 11q; however interstitial deletions have also been repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 33 publications
(37 reference statements)
2
54
0
1
Order By: Relevance
“…Studies in mice have demonstrated that of these four genes, only KCNJ5 and ARHGAP32 are expressed in the brain. 36,38 Interestingly, the 243-kb region deleted in patient 20 also overlaps the distal end of the 2.89-Mb interstitial region reported by Guerin et al 10 in a patient with features of JBS and autism. Although these authors proposed the Kirrel3 gene as a candidate gene for autism in their patient, our findings of ASD in patients without deletion of Kirrel3 suggest that this gene is not causal in at least a subset of patients with distal 11q deletions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Studies in mice have demonstrated that of these four genes, only KCNJ5 and ARHGAP32 are expressed in the brain. 36,38 Interestingly, the 243-kb region deleted in patient 20 also overlaps the distal end of the 2.89-Mb interstitial region reported by Guerin et al 10 in a patient with features of JBS and autism. Although these authors proposed the Kirrel3 gene as a candidate gene for autism in their patient, our findings of ASD in patients without deletion of Kirrel3 suggest that this gene is not causal in at least a subset of patients with distal 11q deletions.…”
Section: Discussionsupporting
confidence: 56%
“…Fisch et al 9 assessed nine patients with JS using the Childhood Autism Rating Scale and determined three scored above the cutoff for autism. Guerin et al 10 described a single patient with a 2.89-Mb deletion in distal 11q who had autistic features and proposed the Kirrel3 gene as a candidate for causing autism in the patient. ASD results from a large variety of genetic causes 30,31 and the results from the current study add to the growing list of genetic syndromes associated with a proportion of children who have ASD.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only seven patients with interstitial deletions at 11q24 (identified by array CGH) have been reported, and none were diagnosed in the newborn period 2, 3, 4, 5, 6, 7, 8. Our case revealed distinct phenotypic findings of a neonate with 11q24 deletion.…”
Section: Discussionmentioning
confidence: 99%
“…Given the deletion sizes in the participants in our study, we may infer that these genes had been deleted in all of our patients, except perhaps for the one with a 2.9 Mb deletion. In that regard, Guerin et al [2012] examined a 4-year-old female with the JBS clinical phenotype and found a small, 2.9 Mb interstitial, as opposed to terminal, deletion at 11q24.2-3. That is, the deleted region did not include either the BSX or NRGN gene.…”
Section: Discussionmentioning
confidence: 96%